2019
DOI: 10.20517/2394-4722.2018.111
|View full text |Cite
|
Sign up to set email alerts
|

PIM-1 inhibition with AZD1208 to prevent osimertinib-induced resistance in EGFR-mutation positive non-small cell lung cancer

Abstract: Aim: The progression free survival of non-small cell lung cancer (NSCLC) patients has been doubled over the last years, but still single epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) lead to incomplete responses. Compensatory signaling pathways are activated upon single EGFR TKIs. We have shown that compounds, which inhibit these pathways, are synergistic with EGFR TKIs. Proviral integration site for Moloney murine leukemia virus (PIM) has been connected to cancer therapy resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Herein, we report that relatively high levels of PIM-1 transcripts were detected in all time points of our study, without any statistically significant difference among them; this observation strongly suggests that this kinase in constantly highly expressed in CTCs and, in parallel, its expression is not affected by osimertinib. However, a strong positive correlation was found between PIM-1 and VIM expression mostly at baseline in contrast to PD samples; although, there is no a clear explanation for this finding, it could be speculated that, according to previous evidence, PIM-1 might indirectly promote cell proliferation by regulating signaling pathways such as IL-6/STAT3 15 , 53 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Herein, we report that relatively high levels of PIM-1 transcripts were detected in all time points of our study, without any statistically significant difference among them; this observation strongly suggests that this kinase in constantly highly expressed in CTCs and, in parallel, its expression is not affected by osimertinib. However, a strong positive correlation was found between PIM-1 and VIM expression mostly at baseline in contrast to PD samples; although, there is no a clear explanation for this finding, it could be speculated that, according to previous evidence, PIM-1 might indirectly promote cell proliferation by regulating signaling pathways such as IL-6/STAT3 15 , 53 .…”
Section: Discussionmentioning
confidence: 81%
“…We also examined PIM-1 expression in CTCs in this patient cohort since it is a promising novel therapeutic target in NSCLC. Many studies indicate the synergistic effects of combination of PIM inhibitor and osimertinib either by preventing the activation of oncogenic signaling pathways 15 or acting through the inhibition of the phosphorylation of STAT3 52 . Herein, we report that relatively high levels of PIM-1 transcripts were detected in all time points of our study, without any statistically significant difference among them; this observation strongly suggests that this kinase in constantly highly expressed in CTCs and, in parallel, its expression is not affected by osimertinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…112 This combination approach has also been shown in non-small-cell lung cancer (NSCLC), where AZD-1208 and osimertinib (an EGFR inhibitor) elicited synergistic effects with respect to cell viability and phosphorylation of STAT3 (ref. 115 ), which, if replicated in PCa, could prevent STAT3-driven promotion of aggressive prostate cancer features. 86 PIM AND RADIOTHERAPY PCa radiotherapy resistance is often linked to and may be attributed to aberrations in the expression of various signaling pathways and genes involved in cell growth and cell death, including downregulation of DOC2/DAB2 (double C2 domain; DAB adaptor protein 2) and P53 (tumor protein P53) and upregulation of MDM2 (ref.…”
Section: Pim and Androgen Deprivation Therapy (Adt)mentioning
confidence: 99%
“…The activation of signalling nodes such as STAT3 and YAP1 as well as the upregulation of different RTKs such as CDCP1 and AXL upon EGFR inhibition also result in EGFR drug resistance (Chaib et al, 2017;. A recent study showed that combining PIM and EGFR inhibitors in EGFR-mutation positive NSCLC cell lines was moderately synergistic but decreased STAT3 phosphorylation, an important signalling node in therapy resistance (Bracht et al, 2019).…”
Section: Resistance To Her2/ Egfr Tyrosine Kinase Inhibitorsmentioning
confidence: 99%